Women’s experiences of intermittent auscultation fetal monitoring in labour: a qualitative study - MacLellan, J; Ade, M; Fitzsimons, B; Kenyon, S; Mulla, S; Pope, C; Sanders, J; Rowe, R (Elsevier, 2024)
Background: Internationally, intermittent auscultation (IA) is recommended for monitoring the fetal heart rate during labour and birth for women with uncomplicated pregnancies. IA can identify changes in the fetal heart rate that may indicate the need for additional care or intervention. IA is a central facet of midwifery practice, but there is little evidence about women’s experience of IA. Aim: Our study aimed to explore women’s experiences of IA in the UK. Methods: Between February and May 2023, 23 women were recruited through social media, service user organisations and charities, for a single episode, online interview or focus group with informed consent. Audio recordings were transcribed and thematically analysed. Findings: The analysis constructed two over-arching themes: ‘Choice takes work’ and ‘Impact of IA monitoring on the labouring woman’. Discussion: Women reported a lack of informed decision-making in relation to intrapartum fetal monitoring. The experience of our participants showed that not all women for whom IA would be recommended according to current clinical guidelines were offered it, while others experienced IA without understanding its function or the availability of other options. Conclusion: Limited antenatal communication from maternity care professionals about fetal monitoring in labour has an impact on women’s opportunities to make informed decisions. A committed approach to informed decision making in the antenatal period could reduce practice variation and better support midwives to support women in their birth choices.